Innovation in Medicine and Healthcare Systems, and Multimedia Proceedings of KES-InMed-19 and KES-IIMSS-19 Conferences - Chen, Yen-Wei.; Zimmermann, Alfred; Howlett, Robert J.; Jain, Lakhmi C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book contains the proceedings of the KES International conferences on Innovation in Medicine and Healthcare (KES-InMed-19) and Intelligent Interactive Multimedia Systems and Services (KES-IIMSS-19), held on 17-19 June 2019 and co-located in St. Julians, on the island of Malta, as part of the KES Smart Digital Futures 2019 multi-theme conference. The major areas covered by KES-InMed-19 include: Digital IT Architecture in Healthcare; Advanced ICT for Medical and Healthcare; Biomedical Engineering, Trends, Research and Technologies and Healthcare Support System. The major areas covered by KES-IIMSS-19 were: Interactive Technologies; Artificial Intelligence and Data Analytics; Intelligent Services and Architectures and Applications. This book is of use to researchers in these vibrant areas, managers, industrialists and anyone wishing to gain an overview of the latest research in these fields.
Part 1: KES-InMed-19 Proceedings -- Chapter 1. Development of a Prototype of a Fast Proximity Authentication System for Electronic Medical Record Terminals Based Virtual Desktop Interface -- Chapter 2. ArchiMate Business Model Patterns to e-Healthcare -- Chapter 3. Monetary and Health Benefits from Better Health Data: Estimating Lives and Dollars Saved from Universal Adoption of the Leapfrog Safety and Quality Standards -- Chapter 4. Success Factors for Realizing Regional Comprehensive Care by EHR with Administrative Data -- Chapter 5. Clinical Decision Support System with Electronic Health Record: Digitization of Research in Pharma -- Chapter 6. Data Augmentation for Building an Ensemble of Convolutional Neural Networks -- Chapter 7. Transfer Learning and Fusion Model for Classification of Epileptic PET Images -- Chapter 8. Multiphase Focal Liver Lesions Classification with Combined N-gram and BoVW -- Chapter 9. SWT-DCT Based Robust Watermarking for Medical Image -- Chapter 10. WatermarkingAlgorithm for Encrypted Medical Image Based on DCT-DFRFT -- Chapter 11. Logistic Map and Contourlet Based Robust Zero-watermark for Medical Images -- Chapter 12. A Sensor Platform for Non-Invasive Remote Monitoring of Older Adults in Real Time -- Chapter 13. Deep Learning for Detecting Breast Cancer Metastases on WSI -- Chapter 14. Advanced Image Processing Algorithms for Breast Cancer Decision Support and Information Management System -- Chapter 15. FDCT and Perceptual Hash Based Watermarking Algorithm for Medical Images.
Keywords: Computational intelligence; Artificial intelligence; Signal processing; Computational Intelligence; Artificial Intelligence; Signal, Speech and Image Processing